A physical activity and socioemotional intervention for residents of a large vulnerable community in Brazil during the COVID-19 pandemic: a randomized controlled study - Torres-Cruz, Mateus; Moura-Alves, Mariana; Lima, Renata Pereira; King, Rachel; dos Santos, Cleber Aparecido; Almeida, Thiago da Silva; Callamari, Frederico Barão; Kolchraiber, Flavia Cristiane; Marega, Márcio; Atalla, Márcio Henrique; Amaro, Edson; Sato, João Ricardo; et al. (Frontiers in Public Health, 2025)
IntroductionThe COVID-19 pandemic exacerbated mental health issues, particularly in vulnerable communities. Non-psychiatric interventions, including psychological emotional regulation, contemplative practices, and physical activity, can be powerful tools for improving mental health, especially in vulnerable populations. The present study evaluates the effect of a novel low-cost Socioemotional and Physical Activity Intervention in a Brazilian large vulnerable community during the pandemic’s final period.Materials and methodsParticipants were adults (18 to 60 years of age) that resided in the Paraisópolis, the third largest favela in Brazil. Recruitment was done through advertising via mobile messaging. Participants were divided into two groups, Intervention (Group I) or Waiting List Control (Group C). Group I participants underwent an in-person Multidimensional Intervention of 1 h per week, for 12 weeks, which was composed of socioemotional skills learning and moderate physical activities, while Group C maintained their usual daily routines. All participants were evaluated before (T0) and after (T1) the Intervention. The evaluation included four validated questionnaires to assess mental health (DASS-21, PANAS, WHO-5 and BRS), IPAQ for evaluating physical activity levels and a physical fitness assessment, which provided quantitative data. A semi-structured interview was also done, which provided qualitative data and was analyzed using a reflexive thematic analysis.ResultsQuantitative data was collected from 88 participants, 43 from Group I and 45 from Group C. We observed a reduction in the scores for depression (DASS−21; Mean difference between evaluations [MD] = −3.2 [± 1.13, SEM], p = 0.006) and negative affects (PANAS, MD = −2.7 [± 0.97], p = 0.012) observed only in the participants of the I group in T1 compared to T0, but not for the C group. We also found a reduction in systolic arterial blood pressure in hypertensive or pre-hypertensive participants after exercise (Group I n = 28; −7.0 [± 2.8] mmHg, p = 0.014), an increase in physical endurance (walk test, MD = +56.0 [±8.7] m, p < 0.001) and flexibility (sit and reach test, MD = +5.12 [±0.85] cm, p < 0.001) only in the I group on T1, compared to T0. The reflexive thematic analysis results suggest that the Intervention not only alleviated negative emotional states, such as anxiety and sadness, but also provided a notable enhancement in participant’s physical vitality, corroborating and complementing the quantitative analysis results.ConclusionThe results presented here indicate that the Intervention presented here has the potential to reduce symptoms correlated with mental disorders and improve physical fitness in residents of a large vulnerable community.